2021
DOI: 10.3390/molecules26164734
|View full text |Cite
|
Sign up to set email alerts
|

Separation and Determination of Chemopreventive Phytochemicals of Flavonoids from Brassicaceae Plants

Abstract: The main aim of this study was to develop a method for the isolation and determination of polyphenols—in particular, flavonoids present in various morphological parts of plants belonging to the cabbage family (Brassicaceae). Therefore, a procedure consisting of maceration, acid hydrolysis and measurement of the total antioxidant capacity of plant extracts (using DPPH assay) was conducted. Qualitative analysis was performed employing thin-layer chromatography (TLC), which was presented to be a suitable methodol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…This is due to the contents of antioxidant substances as associated with species and variety. Radish sprouts have a higher polyphenol content and antioxidant activity compared to broccoli and kale [40]. Because plants have different genetic backgrounds, they show differences in health-promoting properties [41].…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the contents of antioxidant substances as associated with species and variety. Radish sprouts have a higher polyphenol content and antioxidant activity compared to broccoli and kale [40]. Because plants have different genetic backgrounds, they show differences in health-promoting properties [41].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the previous report, the content of glucoraphasatin was highest, whereas the content of gluconapin was lowest in both cultivars. Bajkacz et al [37] reported the presence of 4-hydroxybenzoic acid in radish roots; Goyeneche et al [38] identified gallic acid in radish roots. In line with the previous study [39], catechin was found to be the most abundant phenolic compound in R. sativus root extracts.…”
Section: Discussionmentioning
confidence: 99%
“…It was determined that the application of different heating techniques on kohlrabi (conventional, microwave, and ohmic hating) induced some declines in TPC values [22]. The TPC results of fermented kohlrabi samples corresponded to a prior study in which the phenolic contents and antioxidant activity of 25 different Brassicaceae family vegetables were extensively investigated [23]. The statistical model constructed for TPC was significant at the 95% confidence interval (R 2 = 0.89 and R adj 2 = 0.69) and the boiling time was only important for the TPC model of fermented kohlrabi samples (Table 2).…”
Section: Chemical Properties Of Fermented Kohlrabimentioning
confidence: 94%